The Analisis Kritis Pemikiran Maẖmûd Syaltût Tentang Keotoritasan ijmâ’ Sebagai Sumber Hukum Islam - Mohammad Ridwan; M. Wafa (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
This study discusses the critical analysis of Maẖmûd Syaltût's thoughts on the authority of 'ijma as a source of Islamic law. the aim is to illustrate the importance of understanding 'ijma and how' ijma is seen as a source of Islamic law as well as Maẖmûd Syaltût's view of its authority. This research is a qualitative research using books and academic articles. This is important to bring to the surface as part of knowing 'ijma comprehensively. The authority of 'ijma in Maẖmûd Syaltût's view is a source of Islamic law whose authority and truth are not categorized as qath'i arguments except in ma'lum Min al-Dîn Bi al-Ḏarûrah.